Entropy generation of the laminar and mixed flow of alumina/water nanofluid flow in a two-dimensional rectangular enclosure affected by a magnetic field using the lattice Boltzmann method. (June 2023) - Alqaed, Saeed; Mustafa, Jawed; Almehmadi, Fahad Awjah; Alharthi, Mathkar A; Elattar, H.F.; Refaey, H.A.; Aybar, Hikmet Ş.
Abstract: A study on the entropy generation (EPG) of the laminar and mixed flow of alumina/water nanofluids (NFs) flow in a two-dimensional rectangular enclosure is examined using the Lattice Boltzmann method (LBM). The mixed convection flow is produced in the enclosure utilizing a moving wall and the Boussinesq approximation, which uses the buoyancy force. The moving wall, which is located at the top of the enclosure and has a low temperature, is insulated, as are the other three walls. The side of the enclosure is constantly subjected to a steady magnetic field (MFD). In the center of the enclosure, there are five hot obstacles whose heights range from 0.1 to 0.5. Their distance from the bottom wall and Richardson number (Ri) are also other variables of the problem. Finally, the EPG and Bejan number (Be) are estimated. The results demonstrate that enhancing the distance of obstacles from the bottom wall improves the amount of EPG and Be in such a way that an increment in the distance from 0.25 to 0.4 enhances the amount of total EPG and Be by 18.8% and 9.5%, respectively. An enhancement in the height of obstacles increases the amount of EPG, but the increase of Ri from 0.01 to 100 reduces the amount of EPG. The Be is higher in the parts of the enclosure where the temperature changes are greater.